Impact of Service Quality Perception on Patient Satisfaction in Sangatta at Pupuk Kaltim Prima Hospital - Harmawati, Harmawati; M. Ramdan, Iwan; Sedionoto, Blego (Mulawarman International Conference on Tropical Public Health, 2025)
An ideal situation arises when service providers deliver outstanding service, creating a distinct sense of customer satisfaction that not only drives repeat business but also encourages recommendations to others. This research aims to determine the effect of service quality on patient satisfaction at Pupuk Kaltim Prima Hospital. A cross-sectional study was conducted in September 2023 with 85 respondents, selected through proportional stratified random sampling based on specific inclusion and exclusion criteria. The measuring instruments included a structured Likert-scale questionnaire covering patient satisfaction dimensions. Statistical analysis was performed using descriptive statistics and multiple linear regression analysis with a confidence level of 95% (α = 0.05). The study's statistical tests demonstrated that all five quality dimensions significantly impact patient satisfaction. This study indicates that significant improvements are required in tangibility, assurance, and responsiveness. Additionally, improvements in other dimensions are also necessary to achieve higher levels of patient satisfaction.